Pengaruh Kualitas Produk dan Penanganan Keluhan Pelanggan terhadap Kepuasan Pelanggan Produk Flexible Packaging - Muratin (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2022)
This study aims to analyze the effect of Product Quality and Customer Complaint Handling on Customer Satisfaction of Flexible Packaging Products at PT Sol Graphika. The population in this study were all customers in PT. Sol Graphika in a period of 6 months starting from January 2021 to June 2021, which is as many as 200 customers. The sample in this study were customers of PT. Sole Graphika. The sampling technique used in this study is simple random sampling where the sampling of members of the population is carried out randomly regardless of the strata in the population. The results of calculations with Slovin obtained 67 respondents, the data collected was processed using SPSS. The results showed that the variables of Service Quality and Customer Complaint Handling partially and simultaneously had a significant effect on Customer Satisfaction.